2015
DOI: 10.1002/jcph.678
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Exploratory Pilot Study to Evaluate the Effect of Rotigotine Transdermal Patch on Parkinson's Disease-Associated Chronic Pain

Abstract: Pain is a troublesome nonmotor symptom of Parkinson's disease (PD). This double-blind exploratory pilot study (NCT01744496) was the first to specifically investigate the effect of a dopamine agonist on PD-associated pain as primary outcome. Patients with advanced PD (ie, receiving levodopa) and at least moderate PD-associated chronic pain (≥3 months, ≥4 points on 11-point Likert pain scale) were randomized to rotigotine (optimal/maximum dose ≤16 mg/24h) or placebo and maintained for 12 weeks. Primary efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 46 publications
2
62
0
1
Order By: Relevance
“…As presented in Figure S1, 110 publications involving 24,864 participants were finally included in the present study after screening 1,154 publications according to the inclusion criteria1315161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Figure S1, 110 publications involving 24,864 participants were finally included in the present study after screening 1,154 publications according to the inclusion criteria1315161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PD duration appeared as an independent influencing factor in both models highlighting the prominence of the disease progression over time on the patients’ HRQoL. Interestingly, two studies have now reported the efficacy of dopaminergic (rotigotine patch) 27 and non-dopaminergic (oxycodone with naloxone) 12 agents on pain in randomised placebo-controlled studies. Using the KPPS, the dominant pains responding to the active agents were fluctuation related pain (rotigotine) and musculoskeletal pain (oxycodone with naloxone) and thus a tangible effect of these therapies on HRQoL could be envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…Using the KPPS, the dominant pains responding to the active agents were fluctuation related pain (rotigotine) and musculoskeletal pain (oxycodone with naloxone) and thus a tangible effect of these therapies on HRQoL could be envisaged. 12, 27 …”
Section: Discussionmentioning
confidence: 99%
“…Pain severity was reported in 8 trials using the pain subscale of the Visual Analogue Scale (VAS-P) [17,24,26,27,29,30,33,35], in 8 using section 39 of the Parkinson's Disease Questionnaire-39 [16,22,23,31,32,36,37,39], in 4 using the Likert pain scale [18,19,34,38], in 1 using the King Parkinson's Disease Pain Scale [21], in 1 using question 1.9 of the Movement Disorders Society -Unified Parkinson's Disease Rating Scale (MDS-UPDRS Q1.9) [25], in 1 using the McGill Pain Scale [20], and in 1 trial using the Daily Pain Rating Sheet [28] (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of trials for each identifiable therapeutic intervention category was 3 for dopaminergic agonists [17][18][19], 2 for cannabinoids and opioids [20,21], 3 for surgical methods [22][23][24], 4 for electrical or Chinese therapies [25][26][27][28], 2 for pardoprunox [29,30], 2 for safinamide [16], 1 for catechol-O-methyltransferase (COMT) inhibitors [31], 1 for multidisciplinary team care [32], and 7 for miscellaneous therapies. Miscellaneous therapies included hydrotherapy [33,34], massage therapy [35], gym training [36], mindfulness therapy [37], vibration therapy [38], and power yoga [39] (Table 1, with further intervention details in Appendix 4).…”
Section: Study Characteristicsmentioning
confidence: 99%